Effects of Hormonal Regimens on Ovarian Follicular Activity, Induction of Estrus, Ovulation and Conception Rate in Postpartum Acyclic Sahiwal Cows - Kumar Paikra, Dilip; Kumar Awasth, Manoj; Parveen, Kaiser; Paikra, Dimpal (The Indian Journal of Animal Reproduction, 2025)
The study was conducted on postpartum (≥ 90 days) acyclic Sahiwal cows (n= 24), which were randomly divided into three treatment (n=18) and a control group (n=06). Animals of all three treatment groups were treated with GnRH @ 10 µg i/m on day 0 with intra-vaginal placement of CIDR® containing 1.38 g progesterone for 7 days. Animals were treated with i/m injection of PMSG@ 300 IU on day 5, which was followed by administration of PGF2α (Cloprostenol) @ 500µg i/m on day 7. Animals of Group-I were treated with second dose of GnRH on day 9, while animals of Group-II were administered with Estradiol Benzoate (EB) @ 5 mg i/m. No treatment was given to animals of Group-III on day 9 and animals were observed for sign of estrus and A.I. was carried out at detected estrus up to 72 hrs. Fixed time artificial insemination (FTAI) was carried out at 16-22 hrs after 2nd dose of GnRH in Group-I and EB in Group-II. No treatment was given to animals of control group. Secondary signs of estrus were recorded in all animals of treatment groups. Mean follicular diameters (mm) on day of A.I. were 16.85±1.1, 15.2±0.88 and 14.22±0.65 with ovulation rate of 100%, 83% and 66.6% in animals of Group-I, II and III, which subsequently recorded conception rate of 83.3%, 66.6% and 66.6% respectively. A significant difference (P ≤ 0.05) in mean follicular diameter was observed between animals of Group I and Group III. The highest conception rate was recorded in animals of Group I, which exhibited the largest mean follicular diameter and the highest ovulation rate.